‘I like the people I work with. Maybe I’ll get to meet them in person one day’: teaching and learning practice development with transnational teaching teams - Keevers, Lynne; Lefoe, Geraldine; Leask, Betty; Fauziah K.P., Dawood Sultan*; Ganesharatnam, Sumitha*; Loh, Vincent*; Lim, Jane See Yin* (Informa UK Limited, 2014)
Significant changes have occurred in the international education landscape driven by the need for access to higher education in developing countries. One response to this situation has been the provision of higher education in the developing country via partnership arrangements with overseas institutions. Rapid growth in transnational programmes has resulted in many opportunities for nations seeking to build their capacity, for institutions and for staff and student learning, as well as significant challenges. This research contributes to addressing some of these challenges by focusing attention on teaching and learning practice development with transnational teaching teams. This paper is grounded empirically in an international collaboration between three Australian, one Malaysian and one Vietnamese university. Employing a practice-based approach using multi-site participatory action research, the researchers investigated the professional development needs of transnational teaching teams and their experience working in transnational programmes. The study suggests that for professional development to be effective in transnational education it needs to be collaboratively designed and negotiated, context-sensitive and specific, practice-based and involve teams engaging and learning together in their daily work contexts. Such an approach harnesses the diversity of transnational teaching teams and enhances dialogue and relationships amongst team members.